A Serological Protein Microarray for Detection of Multiple Cross‐Reactive Flavivirus Infections in Horses for Veterinary and Public Health Surveillance. Issue 6 (15th September 2016) - Cleton, N. B.; van Maanen, K.; Bergervoet, S. A.; Bon, N.; Beck, C.; Godeke, G.‐J.; Lecollinet, S.; Bowen, R.; Lelli, D.; Nowotny, N.; Koopmans, M. P. G.; Reusken, C. B. E. M.
Summary: The genus Flavivirus in the family Flaviviridae includes some of the most important examples of emerging zoonotic arboviruses that are rapidly spreading across the globe. Japanese encephalitis virus (JEV), West Nile virus (WNV), St. Louis encephalitis virus (SLEV) and Usutu virus (USUV) are mosquito‐borne members of the JEV serological group. Although most infections in humans are asymptomatic or present with mild flu‐like symptoms, clinical manifestations of JEV, WNV, SLEV, USUV and tick‐borne encephalitis virus (TBEV) can include severe neurological disease and death. In horses, infection with WNV and JEV can lead to severe neurological disease and death, while USUV, SLEV and TBEV infections are mainly asymptomatic, however, and induce antibody responses. Horses often serve as sentinels to monitor active virus circulation in serological surveillance programmes specifically for WNV, USUV and JEV. Here, we developed and validated a NS1‐antigen protein microarray for the serological differential diagnosis of flavivirus infections in horses using sera of experimentally and naturally infected symptomatic as well as asymptomatic horses. Using samples from experimentally infected horses, an IgG and IgM specificity of 100% and a sensitivity of 95% for WNV and 100% for JEV was achieved with a cut‐off titre of 1 : 20 based on ROC calculation. In field settings, the microarray identified 93–100% of IgG‐positive horses with recent WNV infections and 87% of TBEV IgG‐positive horses. WNV IgM sensitivity was 80%. Differentiation between closely related flaviviruses by the NS1‐antigen protein microarray is possible, even though we identified some instances of cross‐reactivity among antibodies. However, the assay is not able to differentiate between naturally infected horses and animals vaccinated with an inactivated WNV whole‐virus vaccine. We showed that the NS1‐microarray can potentially be used for diagnosing and distinguishing flavivirus infections in horses and for public health purposes within a surveillance setting. This allows for fast, cheap, syndrome‐based laboratory testing for multiple viruses simultaneously for veterinary and public health purposes.